233k views
0 votes
Factorise 4(x+y)(3a-b)+6(x+y)(2b-3a)
Please solve this fast.
Show your calculation.​

User Naszta
by
4.6k points

1 Answer

4 votes

Answer:

(-3a+4b) (2x+2y)

Explanation:

Expand.

4(x+y)(3a-b)+6(x+y)(2b-3a) = 4(3ax+3ay-bx-by) + 6(2bx+2by-3ax-3ay)

4(3ax+3ay-bx-by) + 6(2bx+2by-3ax-3ay) = 12ax+12ay-4bx-4by+12bx+12by-18ax-18ay

Calculate like terms.

12ax+12ay-4bx-4by+12bx+12by-18ax-18ay = -6ax-6ay+8bx+8by

Factorise.

-6ax-6ay+8bx+8by = -3a(2x+2y) + 4b(2x+2y)

Factorise further.

-3a(2x+2y)+4b(2x+2y) = (-3a+4b) (2x+2y)

User Pablo Fonseca
by
5.5k points